Hubungan Modal Sosial dengan Tingkat Partisipasi Petani dalam Pembangunan Agrowisata Cau Chocolates di Desa Tua, Kecamatan Marga, Kabupaten Tabanan - DJELANTIK, I MADE ASTRADITA; SARJANA, I MADE; DIARTA, I KETUT SURYA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
The Correlation of Social Capital With The Participation Level of Farmer In The Development Of Cau Chocolates Agrotourism in Tua Village, Marga District, Tabanan Regency.  The rapid development of tourism in Bali not only has a positive impact but also has a negative impact on the agricultural sector. Various negative impacts that arise give rise to efforts to develop alternative tourism. One form of effort to integrate the agricultural and tourism sectors in Bali Province is to develop agro-tourism areas. Cau Chocolates Agrotourism is one of the cocoa agrotourism in Tabanan. The development of agro-tourism cannot be separated from social capital and the participation of farmer groups. The aim of this study is to determine the extent of the correlation between social capital and farmer group participation in the development of Cau Chocolates Agrotourism, Tua Village, Marga District, Tabanan Regency. The data analysis method used is descriptive qualitative and Spearman Rank Correlation Analysis. The results showed that the correlation between social capital and the participation of the Pala Werdhi Farmer Group in the development of Cau Chocolates Agrotourism as a whole was moderate but only significant at three stages. Social capital is significantly correlated with participation in the planning stage, implementation stage, and enjoying the results stage, but not significantly correlated at the evaluation stage. Suggestions that can be conveyed in this study are that further research is needed on the factors driving participation to increase the participation of members of the Pala Werdhi farmer group and there needs to be more assistance and training to the Pala Werdhi farmer group, especially in cocoa cultivation, in order to increase the quantity or quality of the cocoa.